2012
DOI: 10.1080/03630242.2012.707171
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in Southwestern Nigeria: Are There Rural-Urban Differences?

Abstract: The researchers in this study assessed the prevalence of different types and experience of intimate partner violence among 600 women aged 15 to 49 years in selected rural and urban communities in southwestern Nigeria between October and December, 2007. Lifetime prevalence of intimate partner violence was 64% in the rural and 70% in the urban areas. Controlling behavior was the most frequently reported type of intimate partner violence experienced by both groups of women, and sexual violence was reported least.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
6
36
2
Order By: Relevance
“…We have found that a woman's young age and living in urban areas are risk factors for husband/partner controlling behaviour during pregnancy, which is comparable to previous findings in the region and elsewhere 32 36 52. In a slowly but gradually changing Rwandan society, young women are more likely to have more social networks and outgoing activities, which may provoke partners with a tendency towards being controlling.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We have found that a woman's young age and living in urban areas are risk factors for husband/partner controlling behaviour during pregnancy, which is comparable to previous findings in the region and elsewhere 32 36 52. In a slowly but gradually changing Rwandan society, young women are more likely to have more social networks and outgoing activities, which may provoke partners with a tendency towards being controlling.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of 20% in our study is lower than the 33.1% and 42% reported in Malawi and Nigeria, respectively,35 36 but these studies investigate the partner's controlling behaviour before pregnancy, which might have led to higher rates, as pregnancy may be protective against some forms of violence exposure. However, the lower prevalence rates of controlling behaviour may also be a result of changing perceptions about the role of women in Rwandan society as a result of government's efforts to use gender equality as one of the means to achieve social and economic development by empowering women.…”
Section: Discussioncontrasting
confidence: 78%
“…Focus group discussions (FGDs) were conducted to provide formative data for the development of an instrument at UNIV OF PITTSBURGH on August 18, 2015 jiv.sagepub.com Downloaded from (survey questionnaire) for the quantitative study (Balogun et al, 2012). The qualitative data were analyzed to expound personal and cultural perspectives and experiences of IPV among Nigerian women.…”
Section: Methodsmentioning
confidence: 99%
“…Studies from other continents than the US also show an increased risk of partner violence for women in rural areas. For example, a study among 600 women in Nigeria, showed that the lifetime prevalence of physical violence against wives was about twice as high in in rural areas than in urban one's (28% vs. 14%), as was the current prevalence (28% vs. 13%; Balogun, Owoaje & Fawole, 2012). A negative association between urban residence and wife battering was also reported in a large-scale study among almost 14,000 couples in six Sub-Saharan African countries (Alio et al, 2011).…”
Section: 4intimate Partner Violence In Urban and Rural Areasmentioning
confidence: 80%
“…The close-knit nature of rural life, characterized by a lack of anonymity, may prevent women from seeking help for intimate partner violence which in turn can increase the likelihood of abuse. Finally, increased alcohol consumption in rural areas often contributes to the higher prevalence of physical violence against wives, as does the lower level of education and income, the more stressful conditions rural women live in and the lack of sufficient health and intervention programs for interpersonal partner violence (Balogun et al, 2012Peek-Asa et al, 2011.…”
Section: 4intimate Partner Violence In Urban and Rural Areasmentioning
confidence: 99%